Integrationsgestaltung ausbildungsintegrierender Studienprogramme. Eine theorie- und fallstudienbasierte Analyse - Jenert, Tobias; Mordhorst, Lisa Friederike Anna (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

Integrationsgestaltung ausbildungsintegrierender Studienprogramme. Eine theorie- und fallstudienbasierte Analyse - Mordhorst, Lisa Friederike Anna; Jenert, Tobias (Jahrestagung der Gesellschaft für Hochschulforschung)

Jenert, T. & Büker, R. (2023). Designing Self-Regulation interventions for different target groups in Entrepreneurship Education - Jenert, Tobias; Büker, Ronja

Turning Disciplinary Differences from a Brake into a Motor in Higher Education (Collaboration) - Sloane, Hannah Sabrina; Schmöckel, Sabrina

Entwurfsmuster: Fachsensible wissenschaftliche Begleitung - Sloane, Hannah Sabrina; Heidebrecht, Jana

Business Models for Cultural Event Platforms - A Taxonomy Approach - Althaus, Maike; Grieger, Nicole; Vorbohle, Christian; Müller, Michelle; Kundisch, Dennis (Proceedings of the 15th Mediterranean Conference on Information Systems (MCIS))

Turnover-Based Corporate Income Taxation and Corporate Risk-Taking - Amberger, Harald; Siahaan, Fernando; Sureth-Sloane, Caren

Design-Based Research als Erforschung und Gestaltung von Interaktionsprozessen zwischen Wissenschaft und Bildungspraxis - Jenert, Tobias (Wissenschaft trifft Praxis – Designbasierte Forschung in der beruflichen Bildung)
Das Verhältnis zwischen Wissenschaft und Praxis wurde in unterschiedlichen Forschungsansätzen im- mer wieder wissenschaftlich betrachtet. Dennoch ist es notwendig, sich im Rahmen der wissenschafts- theoretischen Konzeption von Design-Based Research (DBR) weiter damit auseinanderzusetzen, denn Interaktion zwischen Wissenschaft und Bildungspraxis ist ein zentrales Merkmal von DBR. Dieser Beitrag befasst sich mit der Frage, wie sich diese Interaktion je nach zugrunde liegendem DBR-Verständnis me- thodologisch fassen lässt. Die Interaktion wird als ein wesentlicher Bestandteil des Erkenntnisprozesses in DBR aufgefasst. Daher wird neben der methodischen Ausgestaltung von Interaktionsprozessen auch methodologisch reflektiert, was die Wissenschaft-Praxis-Interaktion für die Erkenntnis an sich bedeutet.

An interval multi-criteria decision-making model for evaluating blockchain-IoT technology in supply chain networks - Tavana, Madjid; Khalili Nasr, Arash; Ahmadabadi, Alireza Barati; Amiri, Alireza Shamekhi; Mina, Hassan (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Analytic hierarchy process and data envelopment analysis: A match made in heaven - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

A bi-objective hybrid vibration damping optimization model for synchronous flow shop scheduling problems - Tavana, Madjid; Hajipour, Vahid; Alaghebandha, Mohammad; Di Caprio, Debora (Machine Learning with Applications)
Keywords: General Medicine

A general Best-Worst method considering interdependency with application to innovation and technology assessment at NASA - Tavana, Madjid; Mina, Hassan; Santos-Arteaga, Francisco J. (Journal of Business Research)
Keywords: Marketing

Analytical hierarchy process: revolution and evolution - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J. (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

A fuzzy preference programming and weighted influence non-linear gauge system for mission architecture assessment at NASA - Tavana, Madjid; Heidary, Mohammad Saeed; Mina, Hassan (Applied Soft Computing)
Keywords: Software

A Credibility and Strategic Behavior Approach in Hesitant Multiple Criteria Decision-Making With Application to Sustainable Transportation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid; Tena, Emilio Cerda (IEEE Transactions on Fuzzy Systems)
Keywords: Applied Mathematics; Artificial Intelligence; Computational Theory and Mathematics; Control and Systems Engineering

Value Chain digitalization and technological development as innovation catalysts in small and medium-sized enterprises - Marín, Raquel; Santos-Arteaga, Francisco J.; Tavana, Madjid; Di Caprio, Debora (Journal of Innovation & Knowledge)
Keywords: Management of Technology and Innovation; Marketing; Economics and Econometrics; Business and International Management

An integrated decision support framework for resilient vaccine supply chain network design - Tirkolaee, Erfan Babaee; Torkayesh, Ali Ebadi; Tavana, Madjid; Goli, Alireza; Simic, Vladimir; Ding, Weiping (Engineering Applications of Artificial Intelligence)
Keywords: Electrical and Electronic Engineering; Artificial Intelligence; Control and Systems Engineering

A hybrid multi-attribute decision-making and data envelopment analysis model with heterogeneous attributes: The case of sustainable development goals - Soltanifar, Mehdi; Tavana, Madjid; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Environmental Science & Policy)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Spacecraft tracking control and synchronization: An assessment of conventional, unconventional, and combined methods - Deveci, Muhammet; Pamucar, Dragan; Gokasar, Ilgin; Tavana, Madjid (Advances in Space Research)
Keywords: Space and Planetary Science; Aerospace Engineering; General Earth and Planetary Sciences; Atmospheric Science; Geophysics; Astronomy and Astrophysics

A novel median-based optimization model for eco-efficiency assessment in data envelopment analysis - Dellnitz, Andreas; Tavana, Madjid; Banker, Rajiv (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences